Advanced Surface of Fibrous Activated Carbon Immobilized with FeO/TiO2 for Photocatalytic Evolution of Hydrogen under Visible Light. Issue 4 (10th March 2020) - Sharma, Ajit; Thuan, Doan Van; Pham, Thanh-Dong; Tung, Mai Hung Thanh; Truc, Nguyen Thi Thanh; Vo, Dai-Viet N.
Abstract: FeO‐doped TiO2 nanoparticle photocatalysts were immobilized onto the surface of fibrous activated carbon (ACF) via a sol‐gel process. As an adsorbent and photocatalyst, FeO‐TiO2 on immobilized ACFs (FeO‐TiO2 /ACF) greatly improved the photocatalysis rate of hydrogen production as compared with pure TiO2 and ACF‐TiO2 under UV irradiation and visible light. The addition of ACFs surface significantly reduced the photogenerated pairs of electrons‐hole recombination, thereby promoting the photocatalysis action of doped photo‐metal oxides of FeO‐TiO2 . Co‐doping of FeO onto the lattice of the TiO2 approach can improve the absorption activity of visible light through photo‐metal oxide of TiO2 and further enhance hydrogen production under visible light. The photocatalytic fabrics (FeO‐TiO2 /ACF) were effortlessly split out from the experimental solution for re‐utilization and exhibited high stability even after five complete regeneration cycles. Abstract : Hydrogen production and stability of catalytic materials still suffer from low efficiency due to the fast rate of recombination of electron‐holes in the photocatalytic process. Fibrous activated carbon (ACF) served as surface immobilizer to capture co‐doped FeO/TiO2 for improving the sorption of a nanocatalyst onto the porous surface. Stable FeO/TiO2 nanoparticles were immobilized on the ACF surface.